Personal Parish as an Element of the Organizational Structure of the Pastoral Care of Polish Immigrants by the Missionary Oblates of Mary Immaculate in the Archdiocese of Toronto - Kowal, Wojciech (Annales Missiologici Posnanienses, 2016)
The article offers a particular perspective on the organizational structure of the pastoral care of Polish immigrants in Toronto, Canada. The scope of the presentation is limited to the Polish personal parishes in the Archdiocese of Toronto presently entrusted to the Missionary Oblates of Mary Immaculate (Assumption Province). The author’s starting point is an analysis of the implementation of the concept of personal parish in the particular circumstances of the Archdiocese of Toronto, in the period of time before the Second World War when the first Polish personal parishes were formed. The canonical discipline allowed for creation, with the required indult from the Holy See, of non-territorial parishes for persons speaking various national languages or belonging to a specific nation living in the given city or territory. An important step in providing for solid organizational basis for pastoral care of Polish immigrants who in great numbers arrived in Canada after the Second World War, was taken with the signing on July 12, 1949 of particular agreements between the Archdiocese of Toronto and the Oblate Congregation entrusting two Polish national parishes, of Saint Stanislaus and of Saint Casimir, to the Oblates.. A new wave of Polish immigrants arriving in Canada in 1981–1991, due to the introduction of martial law in Poland, coincided with the promulgation of the new Code of Canon Law (1983) which greatly facilitated the task of diocesan bishops in providing pastoral care of immigrants through the means of personal parishes. As the metropolitan region of Toronto is the place in which the great majority of persons of Polish origin have settled, two new personal parishes, of Saint Maximilian Kolbe in Mississauga, ON and, most recently, of Saint Eugene de Mazenod in Brampton, ON were created. The author offers a canonical overview of the present situation after a recent renegotiation of canonical agreements between the Archdiocese of Toronto and Assumption Province of the Missionary Oblates of Mary Immaculate in Canada. Finally, a perspective for the future of pastoral care of persons with Polish ancestry in Canada is proposed. The author concludes that the personal Church structures, including parishes, are beneficial to immigrant population, and thus worthy to be maintained and promoted.